Self‐Assemble and In Situ Formation of Ni1−xFexPS3 Nanomosaic‐Decorated MXene Hybrids for Overall Water Splitting - Du, Cheng‐Feng; Dinh, Khang Ngoc; Liang, Qinghua; Zheng, Yun; Luo, Yubo; Zhang, Jianli; Yan, Qingyu (Advanced energy materials, 2018)
Herein, the authors present the development of novel 0D–2D nanohybrids consisting of a nickel‐based bimetal phosphorus trisulfide (Ni1−xFexPS3) nanomosaic that decorates on the surface of MXene nanosheets (denoted as NFPS@MXene). The nanohybrids are obtained through a facile self‐assemble process of transition metal layered double hydroxide (TMLDH) on MXene surface; followed by a low temperature in situ solid‐state reaction step. By tuning the Ni:Fe ratio, the as‐synthesized NFPS@MXene nanohybrids exhibit excellent activities when tested as electrocatalysts for overall water splitting. Particularly, with the initial Ni:Fe ratio of 7:3, the obtained Ni0.7Fe0.3PS3@MXene nanohybrid reveals low overpotential (282 mV) and Tafel slope (36.5 mV dec−1) for oxygen evolution reaction (OER) in 1 m KOH solution. Meanwhile, the Ni0.9Fe0.1PS3@MXene shows low overpotential (196 mV) for the hydrogen evolution reaction (HER) in 1 m KOH solution. When integrated for overall water splitting, the Ni0.7Fe0.3PS3@MXene || Ni0.9Fe0.1PS3@MXene couple shows a low onset potential of 1.42 V and needs only 1.65 V to reach a current density of 10 mA cm−2, which is better than the all noble metal IrO2 || Pt/C electrocatalyst (1.71 mV@10 mA cm−2). Given the chemical versatility of Ni1−xFexPS3 and the convenient self‐assemble process, the nanohybrids demonstrated in this work are promising for energy conversion applications. Novel 0D–2D nanohybrids consisting of a nickel‐based bimetal phosphorus trisulfide (Ni1−xFexPS3) nanomosaic that decorates the surface of MXene nanosheets are obtained through a facile self‐assembly process. The Ni0.7Fe0.3PS3@MXene reveals low overpotential (282 mV) and Tafel slope (36.5 mV dec−1) for oxygen evolution reaction (OER) and the Ni0.7Fe0.3PS3@MXene || Ni0.9Fe0.1PS3@MXene couple shows good overall water splitting performance.